Theoretical investigation of the sequential reductive dechlorination pathways of chlorobenzenes and chloroanilines - Okutman Tas, Didem; Prytula, Mark T; Mulholland, James A; Pavlostathis, Spyros G; Okutman, Taş Didem (Wiley, 2009)
AbstractThe distribution of product isomers during the sequential reductive dechlorination of pentachloroaniline (PCA) and pentachlorobenzene (PeCB) was examined based on calculated thermodynamic, chromatographic, and electronic properties and then compared to the product distribution achieved by enrichment cultures. The dechlorination pathway analysis based on free energy considerations matched 78% and 67% of the experimental results for the sequential reductive dechlorination of chlorobenzenes (CBs) and chloroanilines (CAs), respectively. Chromatographic properties of CBs and CAs were able to explain some but not all of the reactions in the observed dechlorination pathways. Correlations between the observed dechlorination pattern and electronic properties of the parent compounds were able to explain most of the formation of the observed products. Experimentally observed sequential reductive dechlorination of CBs and CAs were similar to predicted dechlorination pathways based on the charge differential values calculated for the carbon–chloride bonds. Chlorine atoms were removed from the carbon atom that has the highest charge differential or the second highest charge differential. However, although thermodynamic, electronic as well as chromatographic properties of the CBs and CAs are certainly important factors, they may not be sufficient to completely describe the sequential microbial reductive dechlorination. Enzymatic specificity, as well as other factors (i.e., culture acclimation, environmental factors) should be considered for the interpretation of observed sequential reductive dehalogenation pathways of haloorganic compounds. This work provides the most comprehensive analysis to date of theoretical factors that control the sequential reductive chlorination of two homologous series of single‐ring chloroaromatic species. Biotechnol. Bioeng. 2010; 105: 574–587. © 2009 Wiley Periodicals, Inc.
Keywords: Aniline Compounds; Chlorine; Chlorobenzenes; Biotransformation; Metabolic Networks and Pathways